2012
DOI: 10.2298/gsf1206197s
|View full text |Cite
|
Sign up to set email alerts
|

Ecotypical characterization of genetic variation of beech provenances from south-eastern Europe based on the morphometric characteristics of leaves

Abstract: The research was conducted on a provenance test of beech established in the Educational-research centre „Majdanpečka domena” - Faculty of Forestry, University of Belgrade. This paper presents the results of an analysis of the morphometric characteristics of leaves, at the level of 10 provenances in the juvenile developmental stage, originating from South-Eastern Europe. Herbaria material was used to measure the following parameters: leaf length, leaf width, petiole length, leaf base width at 1 cm (from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Following the justification and logic of the project at the international and national level presented in the introductory part of this paper, we can understand the sustainability of reporting on the state of FGR in Serbia� The results of the FGR research, compiled in the country report, represent the starting point for the implementation of short-term, medium-term, and long-term goals and activities� Graph 1. Key country priorities for the conservation of forest genetic resources in the Republic of Serbia Part 1: Differences in the perception of the benefits of FGR in Serbia require a species-specific approach to forest management and the implementation of conservation methods� Part 2: The major causes of forest cover loss are illegal and unplanned logging, as well as increased forest dieback due to extreme weather events, fires, and pest and disease outbreaks� The factors that increase the area of other wooded lands in Serbia are illegal logging and excessive exploitation, habitat loss and fragmentation, forest fires, natural disasters, high nature value farming, and climate change� The Republic of Serbia is one of the six European and 153 world centers of biological diversity (Šijačić-Nikolić, Milovanović, 2010Šijačić-Nikolić et al�, 2014Šijačić-Nikolić et al�, , 2014a� The accurate number of species in the growing stock of the Republic of Serbia will be assessed only after the latest forest inventory has been completed� Only then it will be possible to define trends in the number of individual species� Obviously, disadvantageous past actions have caused serious disturbances in natural ecosystems� They have gradually led to the disappearance or reduction in the number of some species of trees and shrubs, and their habitats have been destroyed or reduced to extremely small areas� The assessment of intraspecific variability of forest trees in Serbia has been performed for the most economically-important species, such as beech -Fagus sylvatica L� (Šijačić-Nikolić et al, , 2012(Šijačić-Nikolić et al, , 2013I ve t i ć , 2009, 2019S to j n i ć et al�, 2010Stojnić, 2013;Nonić et al, 2015Nonić et al, , 2017cNonić et al, , 2019 (Lučić et al�, 2010(Lučić et al�, , 2011(Lučić et al�, , 2011a(Lučić et al�, , 2011bLučić, 2011, etc�), black pine -Pinus nigra JF Arnold (Lučić et al�, 2008(Lučić et al�, , 2010, silver fir -Abies alba Mill� Po p o v i ć et al�, 2017, 2019, etc�), and other species, primarily to define the region of provenance� Investigations of intraspecific variability were also performed for species important from the aspect of conservation and directed utilization of ...…”
Section: Sustainability Of Results and Possibilities For Improving Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the justification and logic of the project at the international and national level presented in the introductory part of this paper, we can understand the sustainability of reporting on the state of FGR in Serbia� The results of the FGR research, compiled in the country report, represent the starting point for the implementation of short-term, medium-term, and long-term goals and activities� Graph 1. Key country priorities for the conservation of forest genetic resources in the Republic of Serbia Part 1: Differences in the perception of the benefits of FGR in Serbia require a species-specific approach to forest management and the implementation of conservation methods� Part 2: The major causes of forest cover loss are illegal and unplanned logging, as well as increased forest dieback due to extreme weather events, fires, and pest and disease outbreaks� The factors that increase the area of other wooded lands in Serbia are illegal logging and excessive exploitation, habitat loss and fragmentation, forest fires, natural disasters, high nature value farming, and climate change� The Republic of Serbia is one of the six European and 153 world centers of biological diversity (Šijačić-Nikolić, Milovanović, 2010Šijačić-Nikolić et al�, 2014Šijačić-Nikolić et al�, , 2014a� The accurate number of species in the growing stock of the Republic of Serbia will be assessed only after the latest forest inventory has been completed� Only then it will be possible to define trends in the number of individual species� Obviously, disadvantageous past actions have caused serious disturbances in natural ecosystems� They have gradually led to the disappearance or reduction in the number of some species of trees and shrubs, and their habitats have been destroyed or reduced to extremely small areas� The assessment of intraspecific variability of forest trees in Serbia has been performed for the most economically-important species, such as beech -Fagus sylvatica L� (Šijačić-Nikolić et al, , 2012(Šijačić-Nikolić et al, , 2013I ve t i ć , 2009, 2019S to j n i ć et al�, 2010Stojnić, 2013;Nonić et al, 2015Nonić et al, , 2017cNonić et al, , 2019 (Lučić et al�, 2010(Lučić et al�, , 2011(Lučić et al�, , 2011a(Lučić et al�, , 2011bLučić, 2011, etc�), black pine -Pinus nigra JF Arnold (Lučić et al�, 2008(Lučić et al�, , 2010, silver fir -Abies alba Mill� Po p o v i ć et al�, 2017, 2019, etc�), and other species, primarily to define the region of provenance� Investigations of intraspecific variability were also performed for species important from the aspect of conservation and directed utilization of ...…”
Section: Sustainability Of Results and Possibilities For Improving Th...mentioning
confidence: 99%
“…Изазови и могућности, у коме су дефинисани приритети, изазови, прилике и препоручене активности за унапређење конзервације ШГР� За потребе комплексног сагледавања тренутног стања (Део 1-5), извршено је прикупљање литературних и теренских података, њихова анализа, обрада и систематизација� У оквиру сваког дела, на основу приказа тренутног стања, извршено је дефинисање слабости и приоритетних циљева за задату област� Део 6 представља сублимацију изазова и прилика свих посматраних области конзервације ШГР и њихово груписање у четири кључна приоритета (Графикон 1): А) Доступност информација о шумским генетичким ресурсима Б) Конзервација шумских генетичких ресурса В) Коришћење, унапређење и газдовање шумским генетичким ресурсима Г) Легислатива, институције и јачање капацитета За сваки кључни приоритет препозната су три до четири изазова, за сваки изазов дефинисана је најмање једна прилика, а за сваку прилику препоручене су конкретне активности за унапређење стања� Извештај је израђен на српском и енглеском језику и, преко Националног координатора (National Focal Point) за Републику Србију, упућен ФАО Комисији за генетичке ресурсе за храну и пољопривреду� Комплексност процеса захтевала је примену модела међуинституционалне сарадње, како би национални истраживачки капацитети у области конзервације ШГР били искоришћени на најефикаснији начин� Највећи изазови процеса израде националног извештаја односили су се на обједињавање свих доступних научних и пројектних резултата и информација на националном нивоу; на допуну недостајућих података о актуелном стању објеката конзервације кроз теренске активности; на препознавање свих снага, слабости, прилика и претњи ШГР Србије и дефинисање сврсисходних акционих мера за очување и унапређење� Према оправданости и логици пројекта, на међународном и националном нивоу, која је приказана у уводном делу овог рада, може се сагледати одрживост процеса извештавања о стању ШГР у Србији� Резултати истраживања ШГР, обједињени у оквиру националног извештаја, представљају полазну основу за имплементацију краткорочних, средњерочних и дугорочних циљева и активности� Главна запажања изнета у оквиру појединачних делова националног извештаја су: Графикон 1. Кључни национални приоритети конзервације шумских генетичких ресурса у Републи-Разлике у перцепцији користи од ШГР у Србији захтевају специфичан приступ газдовању шумама у складу са врстама шумског дрвећа (species-specific) и имплементацију конзервационих метода�Део 2: Главни узроци губитка шумског покривача су илегалне сече, као и непланске сече, као последица појачаног сушења шума, услед појаве екстремних догађаја, пожара и напада штеточина и болести� Покретачи који утичу на повећање површине осталог шумског земљишта у Србији су илегалне сече и претерана експлоатација, губитак и фрагментација станишта, шумски пожари, природне непогоде, пољопривреда високе природне вредности и климатске промене� Србија представља један од шест центара биодиверзитета у Европи и један од 153 светска центра биолошке разноврсности(Šijačić-Nikolić, Milovanović, 2010Šijačić-Nikolić et al�, 2014Šijačić-Nikolić et al�, , 2014a)� Трендове у броју врста у шумском фонду Републике Србије биће могуће проценити тек након што буде завршена нова инвентура шума, која је у току, након чега ће бити могуће дефинисање трендова бројности појединачних врста� Оно што је евидентно је да су негативне активности у прошлости узроковале велике промене у природним екосистемима, што је постепено довело до нестајања или смањења бројности одређених врста дрвећа и жбуња, а њихова станишта су уништена или сведена на изузетно мале површине� Процена унутарврсне варијабилности шумског дрвећа у Србији обављена је за економски најзначајније врсте, као што су: буква -Fagus sylvatica L�(Šijačić-Nikolić et al�, , 2012…”
unclassified
“…This finding showed the presence of genetic diversity, in all beech provenances from the different geographic origins. Although, certain, mostly phenology related studies, reported the existence of a clinal pattern of genetic variability, from east to west (ROBINSON et al, 2013;VITASSE et al, 2009), while a number of other studies, focusing on various functional traits (MÀTYÀS et al, 2009;STOJNIĆ et al, 2015;IVANKOVIĆ et al, 2011;ŠIJAČIĆ-NIKOLIĆ et al, 2012;JAZBEC et al, 2007) showed an ecotypic (unexplained, random) pattern of genetic variability related to seed origin, which effected leaf stomatal traits in F. sylvatica provenances. The results from the present study support findings on ecotypic variation.…”
Section: Resultsmentioning
confidence: 99%
“…Генетички диверзитет, који се у конзервационој биологији помиње од 1970. године, основ је за дугорочан опстанак угрожених врста (Frankel, Bennett, 1970). Варијабилност морфолошких карактеристика била је предмет истраживања различитих дрвенастих врста у Србији, између осталог и на нивоу листова (Nonić et al, 2012a;Šijačić-Nikolić et al, 2012;Devetaković, Šijačić-Nikolić, 2013;Maksimović, Šijačić-Nikolić, 2013;Čortan et al, 2015), плодова и семена (Anderson, Tauer, 1993;Šijačić-Nikolić et al, 2007;2009;Nonić et al, 2012b;, итд. Генетичка варијабилност је кључни фактор у прилагођавању врста променама животне средине, из чега следи да мала варијабилност одређених врста доводи у питање њен опстанак (Čortan et al, 2014).…”
Section: уводunclassified
“…Genetic diversity, which is mentioned in conservation biology since 1970, is the basis for long-term survival of endangered species (Frankel, Bennett, 1970). The variability of morphological characteristics was a subject of research of the variety of woody species in Serbia, among others, at the level of leaves (Nonić et al, 2012;Šijačić-Nikolić et al, 2012;Devetaković, Šijačić-Nikolić, 2013;Maksimović, Šijačić-Nikolić, 2013;Čortan et al, 2015), fruits and seeds (Anderson, Tower, 1993;Šijačić-Nikolić et al, 2007;2009;Nonić et al, 2012b;, etc. Genetic variability has been a key factor in adapting the species to environmental changes, following the fact that a small variation of certain species brings into question its survival (Čortan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%